KANDUNGAN PROTEIN KASAR DAN SERAT KASAR KULIT PISANG KEPOK (Musa paradisiaca) YANG DIFERMENTASI DENGAN Trichoderma viride SEBAGAI BAHAN PAKAN ALTERNATIF PADA FORMULASI PAKAN IKAN MAS (Cyprinus carpio) - A Agustono; Winda Herviana; Tri Nurhajati (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2011)
Cost for feed is about to 60-70% of fishery production costs, but the current feed price is higher as well, so need feed manipulation such as fermentation and feed ingredients substitution that are usually derived from wastes such as kepok banana peels. Fermentation with Trichoderma viride used 4 treatments and 5 replications for 7 days. Inoculum doses were P0 (0%), P1 (3%), P2 (5%) and P3 (5%). Result of this study showed statistically differences (p0.05) for crude protein contents and the best treatment was P2 (5%) and not statistically differences (p0.05) for crude fibre contents. Fermented banana peels with 5% inoculum dose could be used for feed ingredients substitution as isoenergy to replaced rice flour, corn flour and starch in feed formulation for common carp fish (Cyprinus carpio) that includes as likeable cultured fish and one of omnivore fish that tolerable for high amount artificial feed. Keywords: Waste. Kepok banana peels. Trichoderma viride. Substitution. Feed formula for common carp fish.